2022
DOI: 10.1002/ccd.30188
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of larger valve sizing with underfilling in balloon‐expandable transcatheter aortic valve replacement

Abstract: Objectives To investigate the efficacy and safety of larger valve sizing beyond the commercially recommended annular range in transcatheter aortic valve replacement (TAVR) with balloon‐expandable transcatheter heart valve (THVs). Background The clinical implications of larger balloon‐expandable THV implantation with underfilling are poorly evaluated. Methods This retrospective study included 692 consecutive patients who underwent TAVR with SAPIEN3. A total of 271 patients who underwent SAPIEN 3 implantation we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Third, a larger valve with underfilling was frequently used in BE TAV implantation for border zone annulus in our study population to obtain a larger effective orifice area, as previously shown. 16 , 22 Generally, by adjusting the filling volume of BE TAVs with limited sizes, continuously distributed native annular areas are covered. However, because the BE TAV has the structural property of foreshortening with TAV expansion, a larger valve size with underfilling demonstrated a significantly greater TAV height than a smaller valve size with overfilling, albeit with comparable TAV areas.…”
Section: Discussionmentioning
confidence: 99%
“…Third, a larger valve with underfilling was frequently used in BE TAV implantation for border zone annulus in our study population to obtain a larger effective orifice area, as previously shown. 16 , 22 Generally, by adjusting the filling volume of BE TAVs with limited sizes, continuously distributed native annular areas are covered. However, because the BE TAV has the structural property of foreshortening with TAV expansion, a larger valve size with underfilling demonstrated a significantly greater TAV height than a smaller valve size with overfilling, albeit with comparable TAV areas.…”
Section: Discussionmentioning
confidence: 99%